Mitochondria‐associated membrane collapse is a common pathomechanism in SIGMAR1‐ and SOD1‐linked ALS - Seiji Watanabe; Hristelina Ilieva; Hiromi Tamada; Hanae Nomura; Okiru Komine; Fumito Endo; Shijie Jin; Pedro Mancias; Hiroshi Kiyama; Koji Yamanaka (EMBO Molecular Medicine)
Abstract A homozygous mutation in the gene for sigma 1 receptor (Sig1R) is a cause of inherited juvenile amyotrophic lateral sclerosis (ALS16). Sig1R localizes to the mitochondria‐associated membrane (MAM), which is an interface of mitochondria and endoplasmic reticulum. However, the role of the MAM in ALS is not fully elucidated. Here, we identified a homozygous p.L95fs mutation of Sig1R as a novel cause of ALS16. ALS‐linked Sig1R variants were unstable and incapable of binding to inositol 1,4,5‐triphosphate receptor type 3 (IP3R3). The onset of mutant Cu/Zn superoxide dismutase (SOD1)‐mediated ALS disease in mice was accelerated when Sig1R was deficient. Moreover, either deficiency of Sig1R or accumulation of mutant SOD1 induced MAM disruption, resulting in mislocalization of IP3R3 from the MAM, calpain activation, and mitochondrial dysfunction. Our findings indicate that a loss of Sig1R function is causative for ALS16, and collapse of the MAM is a common pathomechanism in both Sig1R‐ and SOD1‐linked ALS. Furthermore, our discovery of the selective enrichment of IP3R3 in motor neurons suggests that integrity of the MAM is crucial for the selective vulnerability in ALS.